Coordinated Optimization of Virtual Power Plants Based on Peer-to-Peer Transactions and Nash Bargaining Approach - Jie Li; Jianwei Guo; Xue Li; Wenteng Liang; Jiannan Zhang; Bin Yang; Fang Liang; Xiao Yu (International Transactions on Electrical Energy Systems)
Distributed power supply has seen a significant rise because of the increasing demand for renewable energy. This rise has also presented various challenges, including independent operation and a lack of coordination among the sources. As a result of these challenges, these distributed power supplies are combined into a virtual power plant (VPP). This paper addresses these issues of interaction and coordination with a proposal for multitype VPP and modeling technology. First, it recommends establishing a peer-to-peer (P2P) transaction framework. Second, Nash bargaining cooperative game theory comes into play, which involves multiple stakeholders in establishing a P2P transaction framework among stakeholders. After that, this proposed model is solved using the alternating direction multipliers method (ADMM). In the end, the verification of this proposed model is achieved by the numerical example that ensures that the VPP alliance operates stably.